STUDI FENOMENOLOGI PENGALAMAN HIDUP ORANG DENGAN GANGGUAN JIWA PASCA PASUNG YANG MENGALAMI PERCERAIAN - Rasmawati, Rasmawati (Journal of Islamic Nursing, 2018)
Pasung as an inhumane act can lower dignity and reduce the quality of life of people with mental illness., They need family support, especially by a spouse to achieve recovery and return to productive. The conditions of divorce and neglect by the living environment can cause problems for people with mental illness. The purpose of this study was to describe the experiences of people with mental illness in living post-pasung life without the support of a spouse.Method: research uses qualitative design with phenomenological approach to explore the life experiences of participants after being abandoned by their wives. Four Participants were chosen by purposive sampling method. Data collection was carried out by in-depth interviews then analyzed by the Colaizzi method.Results: The divorce experienced has an impact on the lives of participants. Two themes produced from this study are grieving in response to financial separation and limitations as obstacles to building a new family.Conclusion: Divorce leaves a deep sadness forpeople winth mental illness so that assistance is needed from family, community and health workers during the grieving process and during the recovery process.